Performance and Emission Characteristics Using Dual Injection System of Gasoline and Ethanol - Bambang Sulistyo; Herminarto Sofyan; Thomas Sukardi; Agus Widyianto (Automotive Experiences, 2023)
This study successfully investigated the engine performance and emission characteristics of a dual injection system that uses both gasoline and ethanol fuels. The study utilized a microcontroller-based control system (PGM-FI) to substitute ethanol fuel injection for gasoline injection. Ethanol fuel was injected at the inlet with three different pressures: 1.0 bar, 1.2 bar, and 1.4 bar, while gasoline injector pressure was fixed at 2 bar. Results showed that substituting ethanol injection with a pressure of 1 bar resulted in a slight decrease in torque and power, but it was the best compared to the other pressures tested. The study found that the use of ethanol injection resulted in improved fuel economy at an ethanol injector pressure of 1 bar with a reduction in SFC of 8.89%. Exhaust emissions were also reduced, with a maximum reduction in CO emissions of 42.54% occurring at a pressure of 1 bar. Similarly, the lowest HC content in exhaust gas was observed at a pressure of 1 bar, which was reduced by 44.48%. However, the results highlighted that ethanol injection pressure could significantly reduce fuel consumption for case A-04 and increase the air-fuel ratio.